Diabetes mellitus as a public health problem; a mini-review on the occasion of world diabetes day 2018 with regard to nephrology - Zaher Khazaei; Malihe Sohrabivafa; Abolfazl Marvi (Society of Diabetic Nephropathy Prevention, 2018)
Type II diabetes is predominantly preventable and managing diabetes by using standard protocols and measures such as promoting healthy living, self-care education in patients, regular screening, with the aim of early diagnosis of disease and its treatment is necessary. These modalities can potentially prevent complications and premature death due to diabetes. Therefore, according to increasing prevalence of diabetes in Iran, along with the growth of aging and lifestyle changes towards urbanization and inactivity, it is necessary to plan for the prevention, care and screening of diabetes in rural areas, especially in the cities, which still have a large proportion of unknown patients.